Induction and regulation of inflammatory bowel disease in immunodeficient mice by distinct CD4+ T-cell subsets. - Maloy, K (2007)
Although the etiology of human inflammatory bowel disease (IBD) has not yet been completely defined, the current prevailing hypothesis is that it is caused by aberrant immune responses, or loss of tolerance, toward components of the intestinal bacterial microflora. During the past decade, several animal models of IBD have been developed that reproduce many features of the human disease. This article will outline one of the best characterized murine IBD models, the "T-cell transfer model" where colitis rapidly develops following adoptive transfer of naive CD4+CD45RB high T cells into immunodeficient scid or RAG-/- mice. This model has also been instrumental in characterizing the potent suppressive activities of CD4+CD25+ regulatory T cells that prevent the development of IBD when cotransferred with the naive CD4+ T cells. The T cell transfer model of IBD is reproducible and easily manipulated and therefore provides an excellent system for the study of immunopathology and immune regulation in the intestine.